2011
DOI: 10.1021/jo200984n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catalytic Properties of 4-Aryl-2,3-dihydro-4H-pyrimido[2,3-b]benzothiazoles for Asymmetric Acyl or Carboxyl Group Transfer Reactions

Abstract: 4-Aryl-2,3-dihydro-4H-pyrimido[2,3-b]benzothiazoles (4-Ar-DHPBs) were synthesized and their catalytic activity and selectivity in kinetic resolution of a secondary alcohol as well as in the Steglich rearrangement and related reactions were evaluated. 4-Aryl-DHPBs showed low enantioselectivity in the acylative kinetic resolution of 1-phenylethanol. Conversely, they catalyzed the Steglich rearrangement with moderate to excellent enantioselectivity, demonstrating the possibility for remote stereocontrol by introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…TheN -benzyl group could be replacedb yN -aromatic substituents while retaining excellent catalytic behavior.E xcellent yields and enantioselectivities were also obtainedw ith regard to N-aromatic substrates possessing para-substituted Ar groups (entries [16][17][18][19][20]. [a] As in Table 1using DBU as abase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TheN -benzyl group could be replacedb yN -aromatic substituents while retaining excellent catalytic behavior.E xcellent yields and enantioselectivities were also obtainedw ith regard to N-aromatic substrates possessing para-substituted Ar groups (entries [16][17][18][19][20]. [a] As in Table 1using DBU as abase.…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol 10 was subsequently transformed to ac hiral bicyclic isothiourea 11,anew class of organic catalyst, in 37% yield and with 85% ee over two steps. [16] Theh ydrogenated product 2l is also au seful intermediatef or the synthesiso f( À)-Paroxetine,at herapeutically importanta ntidepressant. [4] Thus, 2l could be transformedt oc yclic sulfamidate 4 using as imilar method to that described for the synthesiso f9.…”
Section: Resultsmentioning
confidence: 99%
“…[41] It appears that benzannulation of the heterocyclic carbonate leads to only modest enantiocontrol in the isothiourea-mediated rearrangement of these carbonates, consistent with the observations of Okamoto and co-workers. [24] …”
Section: Scope and Limitationsmentioning
confidence: 99%
“…[20] Building upon these precedents, and as part of our existing research programme focusing upon Lewis base catalysis, [21] we have shown that isothioureas such as HBTM 11 and 13 promote the asymmetric O-to C-carboxyl rearrangement of oxazolyl carbonates with high enantioselectivity (up to 94 % ee). [22,23] Notably, recent work by Okamoto has probed the ability of a C(4)-stereodirecting unit within tetrahydropyrimidine-derived isothioureas to promote the asymmetric Steglich rearrangement, [24] whereas Grçger and Dietz have utilised isothioureas for related asymmetric O-to Cacetyl transfer processes. [25] To understand the origins of asymmetric induction in the O-to C-carboxyl transfer process using HBTM 11 we have previously carried out molecular modelling calculations, allowing a simple model for asymmetric induction in this process to be developed ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation